PENGARUH MEDIA SOSIAL ISLAMI, FEAR OF MISSING OUT, DAN LITERASI HALAL TERHADAP MINAT DAN KEPUASAN KONSUMEN - P, Syarmila; Karyono, Otong; Farida, Ida (Izdihar: Jurnal Ekonomi Syariah, 2026)
The development of information technology has increased the use of social media among high school students. Social media is not only used for communication and entertainment, but also for spreading Islamic values and halal product information. Factors such as Fear of Missing Out (FOMO) and halal literacy are assumed to influence consumer interest and satisfaction. This study aims to examine the effect of Islamic social media, FOMO, and halal product literacy on consumer interest and its impact on consumer satisfaction among students of SMA Negeri 2 Bone. This research uses a causal associative quantitative approach with data collected through questionnaires. The sample of this study consisted of students from SMA Negeri 2 Bone and was analyzed using Structural Equation Modeling (SEM-PLS) with SmartPLS. The results show that Islamic social media and halal literacy have a positive and significant effect on consumer interest, while FOMO has no significant effect. The three variables do not directly affect consumer satisfaction; however, consumer interest has a positive and significant effect on satisfaction. Consumer interest also mediates the effect of Islamic social media and halal literacy on satisfaction, while FOMO does not among students of SMA Negeri 2 Bone. Keywords: Islamic Social Media; Fear Of Missing Out; Halal Literacy, Consumer interest; Consumer Satisfaction.